A split-face randomized controlled trial comparing high and low power electrosurgical settings in the treatment of dermatosis papulosa nigra - Ibekwe, Perpetua U.; Atsen, Lynda; Ahmad, Sagiir; Akor, Ogecha; Ukonu, Bob A. (International Journal of Research in Dermatology, 2025)
Background: Dermatosis papulosa nigra (DPN) is a benign skin condition affecting predominantly individuals with Fitzpatrick skin type IV-VI. Electrosurgical treatment is cheaper and readily available, but optimal power settings remain undefined. The aim of this study is to compare the efficacy, safety, and cosmetic outcomes of high- versus low-power electrosurgery settings in the treatment of DPN. Methods: A split-face, evaluator-blinded, randomized controlled trial, 58 participants with Fitzpatrick skin types IV–VI underwent treatment using both high-power and low-power electrosurgical settings (each set at 9 Watts) on opposite sides of the face or neck. Outcomes—lesion clearance, scarring, and pigmentation—were assessed via standardized photography two weeks post-procedure by blinded dermatologists. Results: High-power settings resulted in higher lesion clearance (82.8% versus 77.6%, p<0.001) but were associated with significantly more moderate scarring and pigmentation. Low-power settings showed better cosmetic outcomes (mild scarring: 93.1% versus 87.9%; mild pigmentation: 87.9% versus 72.4%). Overall efficacy, defined as excellent clearance (>85%) with minimal cosmetic side effects, did not differ significantly between groups (p=0.56). Conclusions: Although, low-power setting electrosurgery of DPN offers comparable efficacy to high-power settings, it may require more treatment cycles to eliminate all lesions. It is also the preferable setting for individuals prone to scarring or pigmentary changes.